Pressurized oxy-combustion with low flue gas recycle: Computational fluid dynamic simulations of radiant boilers. (1st October 2016) - Xia, Fei; Yang, Zhiwei; Adeosun, Adewale; Gopan, Akshay; Kumfer, Benjamin M.; Axelbaum, Richard L.
Highlights: A unique boiler is presented for pressurized oxy-combustion of coal with low flue gas recycle. Design method is described for combustion in a pressure vessel with high aspect ratio. 3-D CFD simulations are performed to simulate a full-scale power plant boiler. A long flame is achieved to distribute heat release while minimizing ash deposition. Proper wall heat flux is achieved even when local gas temperature is extremely high. Abstract: Oxy-fuel combustion is considered a promising technology for carbon capture, utilization, and storage (CCUS). One of the primary limitations on full-scale implementation of this technology is the significant increase in the cost of electricity due to a large reduction in plant efficiency and high capital costs. Recently a new concept, namely staged, pressurized oxy-combustion, has been developed in which the flue gas recycle is reduced significantly by means of fuel-staged combustion. At higher pressure the latent heat of condensation of the moisture in the flue gas can be utilized in the Rankine cycle, further increasing the plant efficiency. As determined through ASPEN Plus modeling, this approach increases the net plant efficiency by more than 6 percentage points, compared to first-generation oxy-combustion plants. The early stages of the system involve burning coal in high oxygen concentration, which means the flame temperature is extremely high. New boilers designs are required to handle these extreme conditions. In the present paper, a unique burner and boiler have been designed via computational fluid dynamics (CFD) to effectively and safely burn coal under conditions of elevated pressure and low flue gas recycle. The enclosed jet theory was used to design a combustion system with slow mixing and no external recirculation, which helped minimize flame impingement and ash deposition. A cone-shaped geometry was utilized to minimize the effects of buoyancy in the down-fired, axial-flow system. A 1540 MWth SPOC system was simulated based on this design and the results showed that a relatively uniform distribution of wall heat flux can be achieved and the peak wall heat flux was under a manageable level even though local gas temperature are extremely high.